(untitled) (International journal of medical sciences, 2026)
Today, the number of patients with diabetes mellitus (DM) is increasing year by year in the world. In order to maintain blood glucose levels at a normal level, patients with diabetes mellitus need to set daily norms for themselves, such as diet, insulin, and other means of lowering blood sugar, and strictly adhere to them. For this, patients need to regularly check their blood glucose levels at home or in medical institutions. Currently, glucose measurement is widely used in clinical diagnostic laboratories. When determining the level of glucose in the human body using a standard glucometer, the patient experiences painful sensations. In addition, with each new measurement, the patient can infect himself with some disease or infection that enters the body with blood (for example, hepatitis C, AIDS). Also, daily pricking of the patient's finger with a needle causes various inconveniences for the patient. Therefore, the diagnosis of diabetes mellitus is becoming more and more difficult. In such a situation, the use of non-invasive methods of measuring glucose levels is effective. This article studies the issue of mathematical modeling of glucose level monitoring in diabetes mellitus based on electrical resistance (ER) values ​​obtained from bioactive points (BAPs) informative for the BD of the human body.